Binary masses of the earth crust and biosphere - Mikhail Mikhailovich Labushev (Известия Томского политехнического университета: Инжиниринг георесурсов, 2018)
The relevance of the work is caused by the need to develop and verify mathematical models of geological processes. The main aim of the study is to define natural processes and objects that correspond to mathematical models of equal atomic masses. The methods used in the study is logico-mathematical analysis of average contents of chemical elements in the earth's crust and hydrosphere and molecular masses of photosynthetic products. The results. The analysis of average contents of chemical elements in the earth's crust and hydrosphere substantiates the existence of binary masses «gases - chemical elements». Such masses are proposed to be called Fersman's, or F-masses. F-masses occur in the composition of continental-oceanic crust, continental crust - hydrosphere, soil layer - atmosphere, etc. as mobile dispersed medias with distributed dispersed phases. The state of matter possessing such characteristics is proposed to be called an F-medium. The World Ocean and the upper part of the lithosphere (from the average level of the ocean floor and up to a certain depth from the surface) is considered to be the global binary mass. Binary mass is formed by continents and the World Ocean in the interval of hypsometric marks «the ocean floor - edge of the ocean water»; we must hold the corresponding interface on the continents at 312 m below the level of the World Ocean. It is assumed that this continental-oceanic surface of equal masses is located on the continents approximately at a depth of 1187 m for areas with average hypsometric elevation of 875 m. This depth corresponds to the lower boundary of the formation of near-surface deposits (to the depth of 1-1,5 km) and near-surface deposits with medium-deep (depths from 0,5 to 1-1,5 km) intrusive massifs. F-masses may also be formed as a result of photosynthesis. The formation of such masses presupposes the existence of dispersed medium. The existence of F-masses is probably caused by the previously unknown property of matter to create mutually connected equal masses with gravity and inertial components. The study of F-systems is proposed to be carried out using the Agemarker open source program. The program is based on algorithms of models of equal atomic masses.